The relationship between dietary inflammatory index values and thyroid function in the US adult population: An analysis of the NHANES 2007–2012 cohort - Mingzheng Wang; Xiaofeng Lu; Xiaogang Zheng; Junru Liu (Immunity, Inflammation and Disease, 2023)
Abstract Objective Researchers have developed the Dietary Inflammatory Index (DII) as a tool to quantify the inflammatory potential of a given diet. Higher DII scores indicated a more proinflammatory diet. While inflammation is known to have a strong impact on thyroid function, the precise nature of the association between DII scores and thyroid function has yet to be clarified. This study was conducted with the goal of exploring this relationship in a representative population of adults from the United States. Methods For this study, we used data from the National Health and Nutrition Examination Survey (NHANES). Standardized questionnaires were used to collect demographic and dietary data from the participants, and laboratory tests were used to collect data on the participants' thyroid parameters and other relevant data. Linear regression models and smoothed curve fitting were used to assess the relationship between DII scores and thyroid function, with weighted data analyses and subgroup analyses being conducted as appropriate. Results In total, 7712 subjects were recruited from the NHANES 2007–2012 cohort. Their weighted mean age was 44.87 (0.47) years, mean DII score was 1.41 (0.05). Mean FT3 was 3.20 (0.01) pg/mL and mean TT4 was 7.81 (0.03) µg/dL. In adjusted analyses, higher DII values were related to increases in FT3 (β = .007; p = .027) and TT4 (β = .050; p = .005) levels. Subgroup analyses showed a negative correlation between FT3 levels and DII scores in a population with high urinary iodine concentrations. Conclusion These data indicate that the consumption of a more proinflammatory diet, as evidenced by elevated DII scores, is correlated with significant increases in FT3 and TT4 levels. However, for people with high urinary iodine concentrations, a more proinflammatory diet was associated with lower FT3 levels. Additional research will be vital to clarify the mechanistic basis for these findings.